Optimal timing and safety of the external ventricular drainage in patients with high-grade aneurysmal subarachnoid hemorrhage treated with endovascular coiling. (June 2021) - Ohbuchi, Hidenori; Hagiwara, Shinji; Arai, Naoyuki; Yoneyama, Taku; Takahashi, Yuichi; Inazuka, Mayuko; Kubota, Yuichi; Chernov, Mikhail; Kasuya, Hidetoshi
Highlights: Early ventricular drainage after high-grade SAH has positive impact on the outcome. Delay of the ventricular drainage after high-grade SAH results in poor outcome. Ventricular drainage either before or after ruptured aneurysm coiling is safe. Abstract: The presented retrospective analysis has evaluated the optimal timing and safety of external ventricular drainage (EVD) for acute hydrocephalus after aneurysmal subarachnoid hemorrhage (aSAH). The study cohort comprised 102 patients, 49 of whom underwent EVD at 3–120 h (mean, 16 h) after the clinical onset of aSAH, either before (N = 27) or after (N = 22) ruptured aneurysm coiling. Among those treated with EVD, favorable and fair outcomes at discharge (modified Rankin Scale [mRS] scores 0–3) were noted in 14 (29%) and unfavorable (mRS scores 4–6) in 35 (71%). The former was more common among women (P = 0.019) and patients without chronic arterial hypertension (P = 0.028). The cut-off value for optimal timing of EVD was defined at 13 h after the onset of aSAH. Favorable and fair outcomes were more frequent after early (≤13 h; N = 30) than late (>13 h; N = 19) EVD (40% vs. 11%; P = 0.026), whereas did not differ significantly between those in whom such procedure was done before or after ruptured aneurysm coiling (19% vs. 41%; P = 0.083). In the entire study cohort, 2 patients had re-rupture of the aneurysm, and while both of them were treated with EVD, neither case of complication was directly associated with the procedure and, in fact, preceded it. In conclusion, EVD for management of acute hydrocephalus in patients with high-grade aSAH should be preferably applied within 13 h after the clinical onset of stroke, which may be considered sufficiently safe regardless whether it is performed before or after ruptured aneurysm coiling.